Online Processing of Grammatical Aspect in Subsamples of Preschool Mandarin-acquiring Autistic Children. - Xie, Qian-Qian; Su, Yi (Journal of Autism & Developmental Disorders, 2026)
Grammatical comprehension remains a strength in English-acquiring autistic preschoolers, yet limited studies have examined how autistic children process grammatical constructions in real time, in any language. This study sought to characterize the online processing of grammatical aspect in a diverse sample of Mandarin-acquiring autistic children. Forty-six 3–6-year-old autistic children, further divided into high (N = 23) and low verbal subgroups (N = 23) based on their expressive vocabulary levels, were assessed via Intermodal Preferential Looking (IPL). Children viewed side-by-side renditions of the same event, one of which was ongoing, while the other was completed, paired with familiar verbs with the perfective aspect le or the durative aspect zhe. Both high and low verbal autistic groups demonstrated robust comprehension of le and zhe. Similar to TD children, autistic children in each group showed processing facilities upon the initial presentation of the zhe test audio, but they may be less efficient at le processing. Moreover, the comprehension degree of grammatical aspect correlated negatively with their autism severity scores for the total autistic group; the processing efficiency correlated positively with the production of grammatical aspect for the total and low verbal autistic groups. The findings confirm the strength of processing grammatical aspect in subsamples of preschoolers with autism spanning a wide range of language functioning, suggesting that young autistic group across languages could surmount at least some challenges of aspect acquisition, such as delayed expressive language skills and pragmatic deficits. Additionally, the influencing factors provided insight into the informing intervention strategies that are optimally, developmentally timed.